Social and communication development in autism spectrum disorders : early identification, diagnosis, and intervention - 4 0 16; Charman, Tony,;Stone, Wendy; 5 (New York : The Guilford Press, 2008)
A collection of essays in which leading experts examine new advances in the understanding and treatment of autism spectrum disorders in the first five years of life.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Language.;Language.;Treatment.;Language.;Treatment. -- Autistic children.;Autistic children;Developmentally disabled children;Language disorders in children;Social skills in children.;Communicative disorders in children.;Handicapped children;Language disorders;Social skills.;Communicative disorders; 20; 2